Contracting Masculinity: Gender, Class and Race in a White-Collar Union, 1944-1994 - Cruikshank, Ken (Relations industrielles / Industrial Relations, 2000)
Contracting Masculinity: Gender, Class and Race in a White-Collar Union, 1944-1994, by Gillian Creese, is reviewed.
Keywords: Book reviews; Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; History; Labor Unions; Multiculturalism & pluralism; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z